2012
DOI: 10.3389/fneur.2012.00081
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Early and Late-Onset Alzheimer’s Disease in Neuropsychological Tests

Abstract: Although patients with Alzheimer disease (AD) share clinical and histological features regardless of age of onset, the hypothesis that early onset AD constitutes a distinct subgroup prevails. Some authors suggest that early attention or language impairment constitute patterns of differentiation in terms of neuropsychological profile, between these groups. However, investigations are not consensual in terms of cognitive domains affected in each group. Aim: To investigate whether there is early neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 38 publications
5
32
0
6
Order By: Relevance
“…Other studies have also found a differentiated cognitive profile in the initial presentation of AD according to age of onset [9,[18][19][20]. However, there are some contradictory results [21,22] and there is no current consensus about which cognitive domains are more impaired in each group.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have also found a differentiated cognitive profile in the initial presentation of AD according to age of onset [9,[18][19][20]. However, there are some contradictory results [21,22] and there is no current consensus about which cognitive domains are more impaired in each group.…”
Section: Introductionmentioning
confidence: 91%
“…As in previous studies, age at symptom onset (estimated as reported by family member and/or caregiver) was used to classify patients in EOAD and LOAD groups [5, 7, 10-12, 16, 17, 19, 22, 30]. A standardized interview was used to maximize the reliability establishing the age of onset, as in former research [19,21,33]. The caregiver was asked to identify the ''first problem'' in a structured interview and to give a detailed narrative about it, to further identify the ''earliest episode'' dated by referencing it to a calendar date.…”
Section: Subjects and Clinical Evaluationmentioning
confidence: 99%
“…The few former studies of apraxia in AD mostly included small patient samples, and sometimes tests were not well validated [10,11,12,30,31,32]. One of the major issues of some of the earlier studies is that it is hard to replicate them because it is unknown how or which test was used to assess praxis [12]. Furthermore, in some cases the tests used to measure deficits in praxis seem more likely to measure executive functioning and visuoconstruction [30].…”
Section: Discussionmentioning
confidence: 99%
“…Another small study in AD patients and healthy controls showed that patients performed worse on both ideomotor and ideational apraxia than controls, and especially pantomimes of tool use were most impaired [11]. Furthermore, it has been suggested that patients with early-onset AD were more impaired on praxis than late-onset patients [12]. As can be seen in table 1, tests were not validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation